2014
DOI: 10.5423/ppj.oa.06.2014.0061
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana Remorins Interact with SnRK1 and Play a Role in Susceptibility to Beet Curly Top Virus and Beet Severe Curly Top Virus

Abstract: Remorins, a family of plant-specific proteins containing a variable N-terminal region and conserved C-terminal domain, play a role in various biotic and abiotic stresses, including host-microbe interactions. However, their functions remain to be completely elucidated, especially for the Arabidopsis thaliana remorin group 4 (AtREM4). To elucidate the role of remorins in Arabidopsis, we first showed that AtREM4s have typical molecular characteristics of the remorins, such as induction by various types of biotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…REM1.3's phospho-status defines its plasma membrane nanodomain organization and is crucial for REM1.3-dependent restriction of PVX cell-to-cell movement by regulation of callose deposition at plasmodesmata. This study unveils plasma membrane nanodomain-associated molecular events underlying the plant immune response to viruses.reports of different REM phospho-statuses suggest that the activity of these proteins could be regulated by phosphorylation during plant-microbe interactions 14,15,34,35 .In the present paper, we show that phosphorylation of REM dictates its membrane dynamic and antiviral defense by the reduction of PD permeability. Our data points toward a model whereby viral proteins such as the Coat Protein (CP), TGBp1 from PVX and 30K proteins from Tobacco mosaic virus (TMV) elicit the activation of protein kinase(s), which in turn phosphorylate(s) REM1.3 at its Nterminal domain.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…REM1.3's phospho-status defines its plasma membrane nanodomain organization and is crucial for REM1.3-dependent restriction of PVX cell-to-cell movement by regulation of callose deposition at plasmodesmata. This study unveils plasma membrane nanodomain-associated molecular events underlying the plant immune response to viruses.reports of different REM phospho-statuses suggest that the activity of these proteins could be regulated by phosphorylation during plant-microbe interactions 14,15,34,35 .In the present paper, we show that phosphorylation of REM dictates its membrane dynamic and antiviral defense by the reduction of PD permeability. Our data points toward a model whereby viral proteins such as the Coat Protein (CP), TGBp1 from PVX and 30K proteins from Tobacco mosaic virus (TMV) elicit the activation of protein kinase(s), which in turn phosphorylate(s) REM1.3 at its Nterminal domain.…”
supporting
confidence: 59%
“…Since various studies have reported REM phosphorylation during plant-microbe interactions 14 15 34 35 , we set out to address which kinase phosphorylates REM and whether REM1.3 phosphorylation plays a role in REM-mediated anti-viral defense. Indeed, our experimental findings show that plant PVX sensing induces the activation of a membrane-bound calcium-dependent protein kinase that in turn phosphorylates REM1.3 (Fig 2, Fig EV2, Fig 5).…”
Section: Plant Pvx-sensing Induces the Activation Of A Calcium-dependmentioning
confidence: 99%
See 2 more Smart Citations
“…Remorins from different plant species have been associated with plant defense responses (Jarsch and Ott, 2011; Bozkurt et al, 2014; Son et al, 2014; Fu et al, 2018). Given the fact that the majority of Pseudomonas T3Es target immunity related functions inside the host cell (Büttner, 2016; Khan et al, 2018a), the interaction of NbREM4 with HopZ1a points towards an involvement of NbREM4 in some sort of plant defense response.…”
Section: Resultsmentioning
confidence: 99%